KONSTRUKSI MAKNA GAY BAGI PENGGEMAR MANGA YAOI (FUJOSHI) PADA ANGGOTA KOMUNITAS OTAKU DI PEKANBARU - Ayudyasari, Dara; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Japan‟s pop culture phenomenon has growth in Indonesia. It shown with fans communities/groups that appear which likes Japan‟s typical comic “manga”. The existence of fans groups not only appear in the real world , but also in the virtual world .One of manga fans that really develop in virtual world is fujoshi. Fujoshi is a term for manga yaoi female fans, which manga yaoi itself is one of manga genre focusing on man relationships which are homoromantic and homoerotic. This study aims to determine the motive and meaning for fujoshi on loving yaoi manga in Pekanbaru city.This study used qualitative research methods with phenomenology approach. The subjects of this study consist of five people whose joined on Otaku community in Pekanbaru. To determine informants of this study researcher used purposive sampling technique. On collecting data using deep interview, observation, also documentation. The result of this study shown that because motive of Fujoshi on loving yaoi manga is jealousy motive of female character presence, bored of straight lover, and many bishounen.Whereas in order to motive in this study shown that informants still wants become fujoshi , and want to add the same fujoshi friends, and wishing yaoi manga publish in Indonesia. The meaning that given by fujoshi to gay relationship on yaoi manga was seeing love story in different perspective, gay relationships more romantics than straight story, also life was not like in fairy tale, and their imagination on objects expressed their sexuality.Keywords : Phenomenology, Japanese Pop Culture, Yaoi, Fujoshi